Digital Marketing Innovation And Marketing Capability Moderating Effects On Sme Sales Performance - Suparningsih; Syahra; Astil Harli Roslan (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the influence of Digital Marketing Innovation on Sales Performance with Marketing Capability as a moderation variable in MSMEs in Kendari City. The study used a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) on 165 MSMEs selected through purposive sampling techniques. The sample criteria include MSMEs that have been operating for at least two years, actively utilizing digital media in marketing, and owners or managers are directly involved in marketing decision-making. Data was collected through a five-point Likert scale questionnaire and analyzed using SmartPLS through the evaluation of measurement models (outer model) and structural models (inner model) with bootstrapping procedures. The results of the study show that Digital Marketing Innovation does not have a significant effect directly on Sales Performance. On the other hand, Marketing Capability has a positive and significant effect on Sales Performance. In addition, Marketing Capability has been proven to positively and significantly moderate the relationship between Digital Marketing Innovation and Sales Performance, thus acting as a pure moderator. These findings indicate that the effectiveness of digital marketing innovation is highly dependent on the level of marketing capabilities possessed by MSMEs. Thus, digital transformation in marketing cannot stand alone as a determining factor in sales performance, but must be supported by strong marketing capabilities to be able to generate continuous sales increases.